UMP Bosch Rexroth Academy - Nurul Hazlina, Noordin (2023)
Universiti Malaysia Pahang (UMP)–Bosch Rexroth Academy is a unique collaboration between Bosch Rexroth, the world leader in control and drive industries, and Universiti Malaysia Pahang aimed at accelerating the adoption of Industry 4.0 technologies, such as the internet of things, artificial intelligence, and big data analytics. The Academy provides a platform for businesses and universities to work together on research and development projects that will help drive the industry’s digital transformation.